Grey box identification and adaptive control in a water level system. (November 2019) - Rodriguez, R; Paredes, V; Noa, G; Trucios, L
Abstract: We study the application of Adaptive Control to estimate external disturbances in a Water Level System model, taking advantage of a constructed nonlinear grey box identification that allows to exploit its dynamics. The external disturbances will be specially related to valve manipulations considering limited sensing information using only water height sensors. Our methodology is twofold: (1) Using a grey box model to identify the plant under an operating point and, (2) using adaptive control to react against changes in the system or perturbations on the valve and still lead to a convergent and asymptotically stable controller.